MANAJEMEN BENCANA DALAM PENANGGULANGAN BENCANA DI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA SEMARANG - Radit Bekti Nugroho; Mochamad Mustam; Dyah Lituhayu (Journal of Public Policy and Management Review, 2015)
Disaster in indonesia, it is not a stranger because it must be managed wellso there is a risk that may reduce. This study focused on the readiness of disaster management in regional disaster management agencies semarang city, hether in accordance with the theory of disaster management is pre stage of the disaster , disaster occurs , and after the disaster. And the purpose of this research is want to describe the management of disasters in the disaster on BPBD Semarang city also aware of the barriers faced in disaster management.A method of research in wearing that is descriptive qualitative with conductan interview to the speakers who have been in chose last time to get result is in want. The results obtained through interviews with a focus on three stages is pre disaster , when disaster , and after the disaster that BPBD Semarang city did not have the procedure remains at handling the disaster and monitoring. Hence BPBD Semarang must immediately realize the procedure remainshandling the disasters and their supervision, So that when tackling the disaster can walk with effective and efficient, for coordination must be in the fix that go well and the realization of BPBD ready to cope with the disasters in the city of Semarang